GEO-SPATIAL MODELING OF TRAVEL TIME TO MEDICAL FACILITIES IN MUNA BARAT DISTRICT, SOUTHEAST SULAWESI PROVINCE, INDONESIA - Sula, Nelson; Tosepu, Ramadhan; Mandaya, Iradaf (YCAB Publisher & IAKMI SULTRA, 2018)
Background: Health services are strongly influenced by regional topography. Road infrastructure is a key in access to health services. The geographic information system becomes a tool in modeling access to health services.Objective: To analyze geospatial data of the travel time to medical facilities in Muna Barat district, Southeast Sulawesi Province, Indonesia.Methods: This research used geospatial analysis with classification of raster data then overlaid with raster data such as Digital Elevation Modeling (DEM), Road of Vector data, and the point of Public Health Center (Puskesmas).Results: The result of geospatial analysis showed that the travel time to Puskesmas in Napano Kusambi and Kusambi sub districts is between 90-120 minutes, and travel time to the hospital in Kusambi sub district is required more than 2 hours. Conclusion: The output of this geospatial analysis can be an input for local government in planning infrastructure development in Muna Barat District, Indonesia.